2023
DOI: 10.1038/s41598-023-37495-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting phytochemical diversity of medicinal and aromatic plants (MAPs) across eco-climatic zones and elevation in Uttarakhand using Generalized Additive Model

Abstract: The present study uses a systematic approach to explore the phytochemical composition of medicinal plants from Uttarakhand, Western Himalaya. The phytochemical composition of medicinal plants was analyzed based on (i) the presence of different chemical groups and (ii) bioactive compounds. The Generalized Additive Model (GAM) analysis was used to predict the occurrence of chemical groups and active compounds across different eco-climatic zones and the elevation in Uttarakhand. A total of 789 medicinal plants re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
0
0
0
Order By: Relevance
“…By comparing the quantitative phytochemical presence in the current study with previous studies, researchers can gain insights into the consistency and variability of phytochemical components across different fruit extracts, contributing to the broader understanding of medicinal plant chemistry and potential applications. One study analyzed the phytochemical composition of medicinal plants from Uttarakhand, Western Himalaya, and found that phenolic compounds, flavonoids, and terpenoids were highly abundant classes of phytochemicals (Tiwari et al, 2023). Another study analyzed the phytochemical composition of different parts of milk thistle and found the presence of alkaloids, glycosides, flavonoids, and phenols (Javeed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the quantitative phytochemical presence in the current study with previous studies, researchers can gain insights into the consistency and variability of phytochemical components across different fruit extracts, contributing to the broader understanding of medicinal plant chemistry and potential applications. One study analyzed the phytochemical composition of medicinal plants from Uttarakhand, Western Himalaya, and found that phenolic compounds, flavonoids, and terpenoids were highly abundant classes of phytochemicals (Tiwari et al, 2023). Another study analyzed the phytochemical composition of different parts of milk thistle and found the presence of alkaloids, glycosides, flavonoids, and phenols (Javeed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%